Rare Mucor circinelloides and Fusarium infection in latissimus free flap reconstruction after devastating foot injury in non-neutropenic patient - Holoubek, J; Knoz, M; Lipový, B; Bartošková, J; Kocmanová, I; Hanslianová, M; Krtička, M; Kubek, T (Epidemiologie, mikrobiologie, imunologie, 2020)
Nowadays, free flap reconstruction in devastating lower limb trauma is a standard procedure in reconstructive surgery. The greatest factor directly affecting limb salvage is still the risk of infectious complications, whether local or systemic. Fungal wound infections are not among the most common infection complications in surgery, but their low incidence is compensated for by their fulminant and serious course, as well as severe local tissue destruction and strong angio-invasive potential together with the possibility of dissemination. In this case study, we present an example of a devastating lower leg injury, solved using latissimus free flap reconstruction, with subsequent difficult and prolonged healing, due to an invasive filamentous fungi infection. In the final part of the article, we focus briefly on the occurrence of similar cases in the literature.
Keywords: Foot Injuries; Treatment Outcome; retrospektivní studie; poranění nohy (od hlezna dolů); volné tkáňové laloky; free flap; Humans; reconstruction; Free Tissue Flaps; Plastic Surgery Procedures; Retrospective Studies; infection; zákroky plastické chirurgie; Mucor; fusarióza; lidé; Fusariosis; filamentous fungi; výsledek terapie